Health‐related quality of life in reduced‐intensity hematopoietic cell transplantation based on donor availability in patients aged 50–75 with advanced myelodysplastic syndrome: BMT CTN 1102. Issue 2 (21st November 2022) - Cusatis, Rachel; Martens, Michael J.; Nakamura, Ryotaro; Cutler, Corey S.; Saber, Wael; Lee, Stephanie J.; Logan, Brent R.; Shaw, Bronwen E.; Gregory, Alyssa; D'Souza, Anita; Hamilton, Betty K.; Horowitz, Mary M.; et al.
Abstract: For myelodysplastic syndrome (MDS), allogeneic hematopoietic cell transplantation (alloHCT) is the only available curative therapy. The Blood and Marrow Transplant Clinical Trials Network study 1102 (BMT CTN 1102, NCT02016781) was a multicenter, biologic assignment trial based on matched donor availability in adults aged 50–75 with higher risk de novo MDS who were candidates for reduced‐intensity conditioning (RIC) alloHCT. The primary analysis showed that those who received alloHCT had a survival benefit, but whether this is at the cost of worse quality of life (QOL) has not been described in detail. English‐ and Spanish‐speaking trial participants completed the Functional Assessment of Cancer Therapy—General (FACT‐G), the SF‐36, and the EQ‐5D, at enrollment, every 6 months until 24 months, and 36 months. We compared patient‐reported outcome (PRO) scores between study arms using an inverse probability weighted‐independent estimating equation (IPW‐IEE) model. Between January 2014 and November 2018, 384 subjects (median age 66.7 years, range: 50.1–75.3) enrolled at 34 centers. PRO completion rates were generally high at 65%–78%. The PRO trajectories for both arms were similar, with most decreasing or stable from baseline to 6 months and improving thereafter. Baseline PRO scores were the most consistent independent predictors of subsequent QOL outcomes and survival, even after controlling for clinical and patient‐level factors. For older adults with MDS, the survival advantage associated with donor availability and alloHCT did not come at the cost of worse QOL. These results should reassure older patients and clinicians who prefer a curative approach to treating MDS.